Endurance training does not change the relative intensity at lactate threshold in elderly - Ribeiro Da Mota, G. [UNESP]; Baldissera, V.; Marocolo, M.; Barbosa Neto, O.; Guimarães Faleiros, A. C.; De Oliveira, A.; Ricardo Lopes, C.; Castardeli, E.; Gobbi, S. [UNESP] (My University, 2012)
Aim. The aim of the study was to verify whether endurance training may induce changes on the percentage of peak heart rate (% peak HR) at the lactate threshold (LT) intensity in untrained elderly. Methods. Sixteen healthy men (64.3 ± 4.1 yrs) underwent an incremental test on cycloergometer to determine the LT and the corresponding % peak HR at LT intensity. Afterwards, they were randomly distributed into two groups (n = 8 each): endurance training (ET) and control (C). The ET exercised 3 days a week for 12 weeks. The training session was divided into warm-up (5 min at 50% of LT;), a main part, and a cool-down (5 min 50% below of LT). The main part had a gradual increased volume through the weeks of 2 min. The initial volume on the 1st week was 25 min reaching 47 min at the 12th week. The relative intensity was kept constant (90 to 100% of LT). Results. After 12 weeks, the % peak HR at LT did not change significantly for both groups P > 0.05 (ET 82.9 ± 4.1 vs. 82.5 ± 3.4 and Ç 80.2 ± 7.1 vs. 81.8 ± 7.1). Conclusion. We conclude that endurance training proposed does not change the relative intensity at LT in elderly.
Keywords: Aging; Anaerobic threshold; Physical exercise; lactic acid; adult; aged; anaerobic threshold; controlled study; cool down exercise; cycloergometer; endurance training; ergometer; exercise; geriatric assessment; heart rate; human; human experiment; male; normal human; warm up exercise